1997
DOI: 10.1038/ki.1997.152
|View full text |Cite
|
Sign up to set email alerts
|

Increased atrial natriuretic peptide mRNA expression in the kidney of diabetic rats

Abstract: To investigate whether renal synthesis of atrial natriuretic peptide (ANP) is influenced in diabetes, we measured renal ANP mRNA levels, urine volume, urinary ANP and sodium excretion rates in streptozotocin (STZ)-induced diabetic rats. By using reverse transcription-polymerase chain reaction (RT-PCR) followed by Southern blot analysis, we found that renal cortical and outer medullary ANP mRNA levels in untreated diabetic rats were markedly increased as early as the second day after the onset of hyperglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…This method has proved to be reliable for comparing the changes of a gene product in relatively low abundance. Our previous reports demonstrated that renal ANP mRNA is significantly enhanced and the elevation of urinary ANP excretion correlated well with urinary sodium excretion in diabetic rats (Shin et al 1997) and deoxycorticosterone acetate (DOCA)-treated rats (Lee et al 1996). These findings support the proposal that renal-synthesized natriuretic peptide may be related to the change in water-electrolyte balance (Greenwald et al 1991).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This method has proved to be reliable for comparing the changes of a gene product in relatively low abundance. Our previous reports demonstrated that renal ANP mRNA is significantly enhanced and the elevation of urinary ANP excretion correlated well with urinary sodium excretion in diabetic rats (Shin et al 1997) and deoxycorticosterone acetate (DOCA)-treated rats (Lee et al 1996). These findings support the proposal that renal-synthesized natriuretic peptide may be related to the change in water-electrolyte balance (Greenwald et al 1991).…”
Section: Discussionsupporting
confidence: 67%
“…To determine the relative changes in tissue CNP mRNA expression, the yield of CNP PCR products was normalized to the amount of -actin cDNA amplified from the tissue samples. This method has been used in several studies (Lee et al 1996, Shin et al 1997. Experiments were designed to determine the accuracy of the semi-quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vertebrate kidney is an important target organ for ANP; in fact this hormone helps regulate the volume of extracellular fluid and the electrolyte balance by increasing the secretion of water and salt by directly acting on the kidney [23]. Some authors [40][41][42][43][44][45][46] suggest that the mammalian kidney is also involved in the synthesis of the hormone.…”
Section: Introductionmentioning
confidence: 99%